Construction situation, costs and charges associated with pharmacy intravenous admixture services: multi-center cross-sectional survey based on 137 medical institutions in mainland China - Chunsong Yang; Bing Yao Kang; Lingli Zhang; Dan Yu (BMC, 2020)
Abstract Background To investigate the construction situation, costs and charges associated with pharmacy intravenous admixture services (PIVAS) to provide references for the construction and development of PIVAS in mainland China. Methods A multi-center cross-sectional survey was conducted via a WeChat Group targeting PIVAS leaders in hospitals to investigate the basic situation of PIVAS, including opening time, area, number of PIVAS, equipment, management mode, PIVAS costs and charges, as well as numbers of beds, open wards, and staff, and analyze differences in PIVAS construction at different provincial and hospital levels. Results 137 questionnaires were collected from 29 provinces, representing a response rate of 99.3%. Most participants (88.4%) were from Level III Hospitals. The number of years of operations of PIVAS ranged from 1 to 22 (median: 6). PIVAS site area ranged between 100 and 1973 m2; daily average infusion volume was concentrated in the ranges 0-1000 bags (29.9%, 41/137) and 1001-2000 bags (26.3%, 36/137). In terms of PIVAS management mode, the vast majority used separate pharmacy management (65.0%, 89/137). Only 52.6% (72/137) of PIVAS have standardized charges, and 70.1% (96/137) operate at a loss. The median costs of mixed tumor chemotherapy drugs, total parenteral nutrition, general medicine, antibiotics were 20, 35, 4 and 5 RMB, respectively. With the exception of a few features, PIVAS construction does not obviously differ among different regions and hospital levels. Conclusions In recent years, PIVAS in China has developed rapidly and become relatively large. The main problems are that most provinces lack standards for charges and PIVAS construction differs among hospitals. Therefore, standards for PIVAS construction and charges should be developed to provide a reference for the future development of PIVAS.